Exposure characteristics for congeners, isomers, and enantiomers of perfluoroalkyl substances in mothers and infants - Liu, Yingxue; Li, An; Buchanan, Susan; Liu, Weiping (Environment international, 2020)
•Prenatal and neonatal exposure to PFASs occur globally but differ among countries.•PFOS and PFOA exceed some major environmental toxins in maternal and cord blood.•Exposure to PFOS and PFOA has declined since 2000 while trends for others differ.•Biomonitoring and research at isomeric and enantiomeric levels are essential.•We prefer whole blood over plasma and serum in using blood to assess PFAS exposure. Per- and polyfluoroalkyl substances (PFASs) are ubiquitous in the environment, making it inevitable for humans to be exposed to these pollutants. The exposure begins while in utero and continues in infancy, during the potentially most sensitive early stages of life. This review summarizes the current knowledge on pre- and neo-natal exposures based on more than 200 articles published from 2000 to date. All relevant biological matrices used in the cited studies were included, such as maternal blood, umbilical cord blood, breast milk, placenta, amniotic fluid, fetal organs, newborns’ dried blood spots, and infant serum. We show that such exposures are geographically global with significant discrepancies among countries and continents, and that while the levels of major legacy PFASs (PFOS and PFOA) have declined since 2000, those of others may have not. We also show that levels of PFOS and PFOA exceed those of some major environmental toxins, such as p,p′-DDE, BDE-47, PCB-153, PBB-153, and OH-PBDEs in maternal blood. Given that the behavior and potential effects have an origin in molecular structure, biomonitoring and research at the levels of isomers and enantiomers are critically important. Through critical analysis of these works, we summarize the major achievements, consensus, and the deficiencies of existing research. To our knowledge, this is the first review on the overall internal exposure status of mothers and infants to PFASs during pregnancy and lactation.